Added Value of Soybean Into Tempeh Chips in Kedungjenar Home Industry Centre, Blora Regency - Ayuningtyas, Rizqi Ragil; Ekowati, Titik; Dyah Prastiwi, Wahyu (Jurnal Manajemen & Agribisnis, 2022)
The study aims to describe the characteristics of the home industry, analyze the income of the home industry, and analyze the added value of soybeans from primary products (soybeans) into processed products of tempeh chips. The research was conducted in Kedungjenar Home Industry Centre, Blora Regency, Central Java. The research method used was the census method by sampling saturated with 14 home industries of tempeh chips that process tempeh chips from soybeans as samples. Data were collected by observation and interview with a structured questionnaire. The analytical method used was descriptive analysis, cost analysis, revenue analysis, income analysis, and Hayami's added value analysis. Results showed that the characteristic of the tempeh chips home industry consist of the status is the main business, raw materials are obtained from shops, capital is personal fully funded, and an average labor of 4 people. The total revenue and income of tempeh processing are IDR8,160,000/month and IDR3,556.045/month, respectively. While tempeh chips are IDR21,133,000/month and IDR12,115,779/month, respectively. The added value of tempeh is IDR 16,130/month while the added value of tempeh chips is IDR20,990/month. Therefore, the added value of tempeh chips is greater than the added value of tempeh. The added value ratio for tempeh chips is classified as high (ratio > 40%) and is feasible to work on. Keywords: Hayami method, income, production cost, profit, revenue